No Evidence of Improved Emotion Perception Through Unilateral Hand Contraction. Issue 1 (February 2020) - Stanković, Miloš; Nešić, Milkica
Previous studies have identified improved cognitive performance from unilateral hand contraction to effect contralateral hemisphere activation. As little is known of whether this activation can improve emotion perception, this study examined any differences in perception accuracy and reaction times of matching photographs of human facial expressions presented to the left or right visual fields after left versus right hemisphere activation triggered by unilateral hand contractions. We used photographs of happy, sad, and neutral facial expressions presented briefly and simultaneously (two photographs in each presentation) either unilaterally (intrahemisphere condition) or bilaterally (interhemisphere condition). We recruited 68 university student participants (aged 19–23 years) and randomly assigned half of them to squeeze a dynamometer with the right hand, while the other half squeezed with the left hand, prior to performing the Dimond face-matching task. Matching of happy faces was faster than matching of sad faces. In females (but not males), perception accuracy was higher when stimuli were presented in the right (vs. left) visual field. We found no difference in emotion perception of photographs in either unilateral (intrahemispheric) or bilateral (interhemispheric) stimuli presentations as a function of hand contractions.